2022
DOI: 10.1038/s41598-022-08876-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrophobic moment on membrane interaction and cell penetration of apolipoprotein E-derived arginine-rich amphipathic α-helical peptides

Abstract: We previously developed an amphipathic arginine-rich peptide, A2-17, which has high ability to directly penetrate across cell membranes. To understand the mechanism of the efficient cell-penetrating ability of the A2-17 peptide, we designed three structural isomers of A2-17 having different values of the hydrophobic moment and compared their membrane interaction and direct cell penetration. Confocal fluorescence microscopy revealed that cell penetration efficiency of peptides tends to increase with their hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 59 publications
2
15
0
1
Order By: Relevance
“…It is known that a helical structure is required for the activities of mastoparans [ 17 , 19 ]. A previous study has indicated that a synthetic amphipathic peptide isomer with the highest hydrophobic moment than the other isomers presents with the best membrane interaction ability and forms stable membrane pores with the strongest membrane damage [ 49 ]. Therefore, based on our physicochemical analysis results, it is feasible that mastoparan-AF, -A, -B, -D, -M, and -V may adopt dynamically favorable 3–11 helix structures (instead of α-helix) to facilitate membrane interaction, and thereby result in membrane disruption on the surface of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that a helical structure is required for the activities of mastoparans [ 17 , 19 ]. A previous study has indicated that a synthetic amphipathic peptide isomer with the highest hydrophobic moment than the other isomers presents with the best membrane interaction ability and forms stable membrane pores with the strongest membrane damage [ 49 ]. Therefore, based on our physicochemical analysis results, it is feasible that mastoparan-AF, -A, -B, -D, -M, and -V may adopt dynamically favorable 3–11 helix structures (instead of α-helix) to facilitate membrane interaction, and thereby result in membrane disruption on the surface of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid changes caused by the definition of amphipathicity provoke the rearrangement of the hydrophobic moment, increasing when compared to candidalysin. The increase of hydrophobic moment tends to be correlated to higher efficacy of cell binding and penetration [ 36 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Discriminate between internalization within lipid bilayer or surface [170][171][172][173][174][175][176][177][178][179] Electron Microscopy Peptide distribution and membrane modification induced by the peptide.…”
Section: Techniquesmentioning
confidence: 99%
“…[6,170] One such study, that compared the membrane interaction with hydrophobic properties and amphipathicity of the peptides, showed that cell penetration efficiency tends to increase with their α-helical and amphipathicity content, but, with the highest hydrophobic moment, CPPs predominantly remain on plasma cell membranes. [171] Another group has explored the neuroprotective effects of two arginine rich CPPs, containing TAT fragments, by CD experiment aimed to characterize the interaction of these peptides with an artificial neuronal membrane. Modification in the intensity of the peptide CD signal in combination with the redshift effect was symptomatic of the formation of ordered structures during the interaction with neuronal mimicking liposomes.…”
Section: Circular Dichroismmentioning
confidence: 99%